Politics, ethnicity and jostling for power : the evolution of institutions of Muslim leadership and Kadhiship in colonial Kenya, 1895-1963 - Mwakimako, Hassan Abdulrahman (Department of Religious Studies, 2014)
Summary in English.||Bibliography: leaves 265-272.